Patelofemoral pain syndrome analysis in female individuals practicing crossfit: a cross-sectional study (Research, Society and Development, 2022)
Goal: Evaluate knee functionality and symptomatology concerning patellofemoral pain syndrome in women practicing CrossFit activity. Methods: This is a cross-sectional study for non-probabilistic convenience. Through an online questionnaire, a total of 32 questions were asked relevant to the subject addressed. The questions were focused on the anatomy of women and related to pain during various exercises and in their activities of daily living. Result: In the result, it can be observed that women with high BMI have more pain in the patellar region when compared to the others. The exercises practiced in CrossFit cause and/or aggravate this injury, because, in addition to being overweight, there is still excessive weight lifting. The practices of squatting, jumping, and running with weights, further overload the joints, increasing the pain of the region. Worsening of injuries interferes with women's DLA’s, making activities simple such as walking, sitting, lifting, squatting highly painful.